The Viking chief's marriage alliance - Morris, Lucy (Romance fiction writer) (Harlequin historicals., 2021)
"When Thorstein Bergson rescues a beautiful woman from a storm-tossed longship, he little expects to broker a powerful marriage alliance with her. This high-status ice queen is not the comfortable wife the warrior chief is seeking. But maybe the bittersweet pain in Gyda's eyes hides another woman beneath? The one he tasted that first night when she'd kissed him with such pent-up longing..."--